Self-Consciousness, Self-Monitoring and the Behavioral Confirmation of the Self-Concept - Huić, Aleksandra; Kamenov, Željka (2008)
Individuals often take actions that provide them with opportunities to act upon and maintain their self-concept. Correspondence between one’ s self-concept and one’ s behavior is likely to be moderated by levels of one’ s self-consciousness and self-monitoring. Self-consciousness is a tendency of individuals to focus onto themselves. In doing this they can either direct their attention to their private aspects (their inner thoughts and feelings) or to their public aspects (what is seen by others). Self-monitoring refers to behavioral regulation based on relevant situational and interpersonal cues. These two individual difference variables should, in conjunction, help explain how individuals would behave in relevant situations in order to confirm their conceptions of self. Our goal was to test these theoretical assumptions in a highly self-relevant real life context. The study was conducted as a part of a communication skills course. 173 students taking the course, age ranging from 26 to 53, participated in the study. As a measure of self-concept we administered a self-report measure of communication skills in interpersonal relations. Self-consciousness scale (Fenigstein, Scheier and Buss, 1975) and Self-monitoring scale (Snyder, 1974) were also administered. During the course students had the opportunity to express their communication skills through their active participation in workshops and through demonstrating their theoretical knowledge. They also had a choice whether to prepare and give a public presentation or not. We examined how self-consciousness and self-monitoring contributed to behavioral confirmation of the self-concept in specified student activities.
Projekt MZOS
ENG